Methionine Sulfoxide Reductases of Archaea - Julie A. Maupin-Furlow (MDPI AG, 2018)
Methionine sulfoxide reductases are found in all domains of life and are important in reversing the oxidative damage of the free and protein forms of methionine, a sulfur containing amino acid particularly sensitive to reactive oxygen species (ROS). Archaea are microbes of a domain of life distinct from bacteria and eukaryotes. Archaea are well known for their ability to withstand harsh environmental conditions that range from habitats of high ROS, such as hypersaline lakes of intense ultraviolet (UV) radiation and desiccation, to hydrothermal vents of low concentrations of dissolved oxygen at high temperature. Recent evidence reveals the methionine sulfoxide reductases of archaea function not only in the reduction of methionine sulfoxide but also in the ubiquitin-like modification of protein targets during oxidative stress, an association that appears evolutionarily conserved in eukaryotes. Here is reviewed methionine sulfoxide reductases and their distribution and function in archaea.